2010
DOI: 10.1111/j.1442-2050.2010.01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of suspected esophageal foreign body in adults

Abstract: Foreign bodies should not be allowed to remain in the esophagus beyond 24 hours after presentation. However, some patients with esophageal foreign body ingestion do not come to the hospital immediately and may delay medical intervention from the time of ingestion. The aim of this study was to investigate the outcomes of adults with suspected esophageal foreign body ingestion according to the time of ingestion and types of foreign bodies. A total of 326 adult patients (151 men and 175 women) were analyzed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 28 publications
4
65
2
6
Order By: Relevance
“…These data are in accordance with previous studies in adults that show an esophageal FB extraction rate of 91.4% by FE in adults [20], and reports of incidences of complications associated with endoscopic treatment of esophageal impaction ranging from 15% to 42% [21–23]. We observed a slightly higher rate of complications, possibly because we frequently (80%) found that the impacted objects in our patients were sharp FBs, such as bones, dentures, jujube pits, and pills covered by foil packages.…”
Section: Discussionsupporting
confidence: 94%
“…These data are in accordance with previous studies in adults that show an esophageal FB extraction rate of 91.4% by FE in adults [20], and reports of incidences of complications associated with endoscopic treatment of esophageal impaction ranging from 15% to 42% [21–23]. We observed a slightly higher rate of complications, possibly because we frequently (80%) found that the impacted objects in our patients were sharp FBs, such as bones, dentures, jujube pits, and pills covered by foil packages.…”
Section: Discussionsupporting
confidence: 94%
“…Odynophagia and oesophageal ulcers: One retrospective cohort study 19 showed a significantly lower incidence of odynophagia and oesophageal ulcers in oesophageal foreign body (all types) patients treated within 24 hours. Oesophageal perforation: Soft food boluses have a lower propensity to perforate the oesophagus compared to sharp objects like bones 1 although any oesophageal foreign body compressing the mucosa for a prolonged period may theoretically cause ischaemia.…”
Section: Surgery Complicationsmentioning
confidence: 99%
“…are the most common foreign bodies ingested by adults. [4][5][6][7][8][9] Majority of the foreign bodies are radio-opaque, and requires radiological screening the entire gastro-intestinal tract particularly in children and psychiatric patient for detection of multiple foreign body.…”
Section: Discussionmentioning
confidence: 99%